An Overview on The Use of Lemna minor L. in the Field of Health and Nutrition - Eda Sönmez Gürer; Evren Algın Yapar (Turkish Journal of Agriculture: Food Science and Technology)
Lemna minor L. is an aquatic plant that is resistant to hard conditions, is a fast growing, rapidly multiplying vascular floating macrophyte, and is widely distributed in wetlands in our country and around the world. Lemna minor L., also known as duckweed, contains essential nutrients such as proteins, carbohydrates and fats, as well as various secondary metabolites that are beneficial for humans. Therefore, it is a remarkable source of alternative food. In addition to its traditional medical use, it is thought that taking into account in the development of herbal medicines and cosmetics today in the light of scientific studies will be beneficial in terms of developing value-added products and bringing them into the economy. In this review, studies and articles on the usability of Lemna minor L. in the field of health and nutrition are reviewed and presented with an overview.